Effect of Leadership Style and Employee Competence on Employee Performance Through Organizational Citizenship Behavior - Bambang Sunatar (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The purpose of this study is to determine the effect of leadership style and employee competence on employee performance through organizational citizenship behavior. The research is included in descriptive quantitative research. The population was government employees of Sorong city, West Papua with a total sample of 30 employees. The sample was taken using a simple random sampling technique. The data analysis technique used Partial Least Squares (PLS). The results showed that there was a significant negative effect between leadership style on employee performance, a significant positive effect between leadership style on organizational citizenship behavior, a significant positive effect between employee competence variables on employee performance, a significant positive effect between employee competence on organizational citizenship behavior, a significant negative effect between organizational citizenship behavior on employee performance, a significant positive effect between leadership style on employee performance mediated by organizational citizenship behavior, and significant positive influence between employee competence on employee performance mediated by organizational citizenship behavior.